2022
DOI: 10.3389/fpain.2022.925013
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture as a Complementary Therapy for Cancer-Induced Bone Pain: A Systematic Review and Meta-Analysis

Abstract: BackgroundCancer-induced bone pain (CIBP) is a special type of cancer pain and lacks safe and effective treatments. Acupuncture is a potentially valuable treatment for CIBP, studies evaluating the effect of acupuncture on CIBP have increased significantly, but the safety and efficacy of acupuncture to control CIBP remains controversial.ObjectiveTo provide the first meta-analysis to evaluate the safety and efficacy of acupuncture in CIBP management.Data SourcesCNKI, CBM, Wanfang, VIP Database, PubMed, Embase, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Full-text reading of the remaining literature further excluded 7 publications. Finally, 14 publications 23 -36 were included. The process of publication selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Full-text reading of the remaining literature further excluded 7 publications. Finally, 14 publications 23 -36 were included. The process of publication selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Ten reviews 24,26,28,[30][31][32][33][34][35][36] reported pain relief rates after the intervention. The results of these reviews 24,26,28,[30][31][32][33][34][35][36] indicated that the pain relief rate in the intervention group (acupuncture plus drug therapy) was significantly higher than that in the control group (drug therapy). However, acupuncture treatment alone was not superior to drug in improving the pain relief rate.…”
Section: Summary Of Included Outcomesmentioning
confidence: 99%
See 3 more Smart Citations